Cocaine cardiovascular effects and pharmacokinetics after treatment with the acetylcholinesterase inhibitor donepezil. Issue 5 (8th July 2016) - Grasing, Kenneth; Mathur, Deepan; DeSouza, Cherilyn; Newton, Thomas F.; Moody, David E.; Sturgill, Marc
Abstract : Background: In rodents, cholinesterase inhibitors can cause sustained decreases in the reinforcing effects of cocaine. Nonetheless, cocaine is metabolized by butyrylcholinesterase (BuChE), raising concerns that cholinesterase inhibition could increase its peripheral concentrations, perhaps augmenting toxicity. Although donepezil is approved for use in patients and selective for inhibiting acetylcholinesterase over BuChE, no studies have reported cocaine bioavailability in human subjects receiving donepezil. Methods: Twelve cocaine‐dependent veterans received three days of treatment with either oral placebo or 5 mg daily of donepezil, followed by cross‐over to the opposite treatment. During both oral treatments, double‐blind intravenous cocaine was administered at .0, .18, and .36 mg/kg in a laboratory setting, followed by determinations of heart rate, blood pressure, and plasma concentrations of cocaine and major metabolites. Results: Intravenous cocaine produced dose‐related increases in systolic blood pressure that were most pronounced over the initial 30 minutes after treatment. Oral donepezil attenuated drug‐induced elevations of systolic blood pressure following low‐dose cocaine (.18 mg/kg). No significant difference in blood pressure following treatment with placebo or donepezil after high‐dose cocaine (.36 mg/kg). Peak values of blood pressure and heart rate were unaffected by donepezil. Plasma concentrations of cocaine and metabolites did not differ in donepezil‐ and placebo‐treated participants. Conclusions and Scientific Significance: We conclude that donepezil can attenuate drug‐induced increases in systolic blood pressure following low‐dose cocaine, but does not otherwise modify the cardiovascular effects of intravenous cocaine. Clinically significant changes in cocaine bioavailability and cardiovascular effects do not occur following this dose of donepezil. (Am J Addict 2016;25:392–399)